ANALISIS PERATURAN MENTERI NEGARA LINGKUNGAN HIDUP REPUBLIK INDONESIA NOMOR : 07 TAHUN 2006 TENTANG TATA CARA PENGUKURAN KRITERIA BAKU KERUSAKAN TANAH UNTUK PRODUKSI BIOMASSA ( Tinjauan Ekonomi Lingkungan) - BADERAN, DEWI WAHYUNI K (Sainstek, 2009)
Mankind activities bring influence towards the environment. This influence causes the damage of land surface. The activities indicate that human beings merely pursue the economic advantages, regardless of such impact. Economic activities and the rapid growth of population have put pressure on the nature balance which leads to the destruction of environment. It is necessary to notice that the land damage and the decline of environment quality will influence the lives of mankind. In order to minimize the impact of environment quality decline, the State Minister of Environment has issued a Law No.: 07 year of 2006 concerning the procedures for analyzing the standard criteria of land damage for Biomassa production. The government issued the law after considering the way of how to cope with environmental problems, particularly the land damage which harms a lot of farmers. Before determining the criteria of environment destruction, it is important to note the following things: (a) the implementation of policy which supports the people and the environment, (b) the implementation of the land damage criteria that has already been done, (c) the control and the law enforcement for the possible violations, (d) evaluation and sustainable system which is effective and efficient. Meanwhile, regarding the compilation of the standard and policy instrument, it is necessary to follow some steps namely: (a) standard establishment, (b) regulated standard, (c) choice of policy instrument.